2017
DOI: 10.1111/jcmm.13420
|View full text |Cite
|
Sign up to set email alerts
|

LncRNADANCR contributes to lung adenocarcinoma progression by sponging miR‐496 to modulate mTOR expression

Abstract: Long non‐coding RNAs (lncRNAs) have emerged as new and important regulators of pathological processes including tumour development. In this study, we demonstrated that differentiation antagonizing non‐protein coding RNA (DANCR) was up‐regulated in lung adenocarcinoma (ADC) and that the knockdown of DANCR inhibited tumour cell proliferation, migration and invasion and restored cell apoptosis rescued; cotransfection with a miR‐496 inhibitor reversed these effects. Luciferase reporter assays showed that miR‐496 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 32 publications
3
58
2
Order By: Relevance
“…One critical mechanism by which lncRNAs regulate gene expression is acting as ceRNAs to sponge targeted miRNAs (Salmena et al, 2011). This is also true for DANCR, not only because several miRNAs have been identified as direct targets of DANCR, but also the function of DANCR is prominently mediated through downregulating the expression of these miRNAs, as reported by recent studies Lu et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Xu et al, 2018;Yang et al, 2018), to name a few. Combining predictive methods and some biochemical experiments, we demonstrate that miR-874-3P is a new binding target of DANCR and that by suppressing the inhibitory effect of miR-874-3P on ATG16L1 expression via interacting and decreasing miR-874-3P level, DANCR possesses an ability to upregulate ATG16L1 expression.…”
Section: Disscussionmentioning
confidence: 90%
“…One critical mechanism by which lncRNAs regulate gene expression is acting as ceRNAs to sponge targeted miRNAs (Salmena et al, 2011). This is also true for DANCR, not only because several miRNAs have been identified as direct targets of DANCR, but also the function of DANCR is prominently mediated through downregulating the expression of these miRNAs, as reported by recent studies Lu et al, 2018;Wang et al, 2018a;Wang et al, 2018b;Xu et al, 2018;Yang et al, 2018), to name a few. Combining predictive methods and some biochemical experiments, we demonstrate that miR-874-3P is a new binding target of DANCR and that by suppressing the inhibitory effect of miR-874-3P on ATG16L1 expression via interacting and decreasing miR-874-3P level, DANCR possesses an ability to upregulate ATG16L1 expression.…”
Section: Disscussionmentioning
confidence: 90%
“…Both assays revealed that DANCR was primarily located in the cytoplasm (Fig. 4A and B), which suggested that DANCR can regulate downstream signaling at the posttranscriptional level [21,31]. To investigate the underlying mechanism by which DANCR regulates FOXO3, we analyzed the secondary structure of DANCR.…”
Section: Lncrna Dancr Is Associated With Auf1mentioning
confidence: 98%
“…The lncRNA DANCR (differentiation antagonizing non-protein coding RNA) is a newly identified lncRNA with pivotal roles in cell proliferation, migration, invasion, and stem cell differentiation [20][21][22]. DANCR was first described as a lncRNA that blocks the differentiation of the epidermal progenitor cells [23,24].…”
mentioning
confidence: 99%
“…Fox example, LINC00968 acts as an oncogene in NSCLC by activating Wnt signaling pathway 10 . DANCR acts as a ceRNA for miR-496 to regulate the expression of mTOR, thus promoting NSCLC growth 11 . LINC00473 is highly induced by LKB1 inactivation and LINC00473 upregulation promotes the growth of LKB1-inactivated NSCLC cells 12 .…”
Section: Introductionmentioning
confidence: 99%